Novel adaptive duplex technique adapted to future mobile communication system - ZHANG Ying-hai; WANG Wei-dong; DONG Yu; ZHOU Kai-jie (Tongxin xuebao)
The concept of adaptive duplex was introduced.Based on it,a novel adaptive duplex transmission technique-asymmetric frequency division duplex（AFDD） was proposed,which considers the asymmetric characteristics of future communications system both in service demand and electromagnetic radiation effects.AFDD has the advantage inheriting from FDD;furthermore,it can allocate frequency resources in downlink and uplink dynamically like TDD which increases the usage efficiency of radio resources.Applying AFDD to CDMA communication system,it is proved that AFDD improves that system’s performance compared with FDD.